2016
DOI: 10.1016/j.healun.2016.01.499
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin 4 Receptor-α Potentiates the Effect of Oncostatin M Receptor on the Release of FGF23 by Cardiomyocytes

Abstract: are combined, there are concerns regarding delays to institution of liver cold preservation. The aim of this study was to develop a combined DCD heart and liver retrieval protocol in a pig model with subsequent normothermic machine perfusion (NMP) of both organs to mitigate warm ischemic damage. Methods: Pigs (n= 12; 60-70 kg) were anesthetised. Baseline observations were recorded. After sternotomy, and laparotomy, ventilatory support was withdrawn to mimic DCD conditions. Death was defined as equalisation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similar properties of OSM apply to IGF-1-treated cardiomyocytes [10]. Furthermore, integration of IL-4 receptor signals-which cause only minor changes in FGF23 secretionstrongly potentiate FGF23 release [110]. Another important feature of OSM is its ability to affect the myocardial environment by inducing the strong production and release of potent extracellular proteins (Table 1) such as TIMP-1, interleukin-6, and the regenerating islet-derived proteins (Reg1 and Reg3 chemokines) [9,11].…”
Section: Effects Of Type I and Ii Receptor Activation On Cultured Car...mentioning
confidence: 81%
See 1 more Smart Citation
“…Similar properties of OSM apply to IGF-1-treated cardiomyocytes [10]. Furthermore, integration of IL-4 receptor signals-which cause only minor changes in FGF23 secretionstrongly potentiate FGF23 release [110]. Another important feature of OSM is its ability to affect the myocardial environment by inducing the strong production and release of potent extracellular proteins (Table 1) such as TIMP-1, interleukin-6, and the regenerating islet-derived proteins (Reg1 and Reg3 chemokines) [9,11].…”
Section: Effects Of Type I and Ii Receptor Activation On Cultured Car...mentioning
confidence: 81%
“…Moreover, OSMR signaling is likely to be even more complex, as it has been demonstrated that not only does the use of other activated receptors lead to the amplification of OSM signals but also that the OSMR is directly involved in unrelated receptor signaling cascades. In OSM-treated cardiomyocyte cultures, activation of the interleukin-4 receptor (IL-4R) strongly enhanced the release of FGF23, whereas the IL-4 receptor ligands IL-4 and IL-13 themselves did not trigger secretion [110]. FGF23 was initially identified as an endocrine hormone affecting mineral metabolism and decreasing phosphate reabsorption in the kidneys, but recent studies demonstrated its association with cardiac diseases [11,17].…”
Section: The Complexity Of Determining the Function Of Osm In Human H...mentioning
confidence: 99%